ViPErLEED package I: Calculation of I(V) curves and structural optimization - Florian Kraushofer; Alexander M. Imre; Giada Franceschi; Tilman Kißlinger; Erik Rheinfrank; Michael Schmid; Ulrike Diebold; Lutz Hammer; Michele Riva (Physical Review Research)
Low-energy electron diffraction (LEED) is a widely used technique in surface-science laboratories. Yet, it is rarely used to its full potential. The quantitative information about the surface structure, contained in the modulation of the intensities of the diffracted beams as a function of incident electron energy, LEED I(V), is underutilized. To acquire these data, only minor adjustments would be required in most experimental setups, but existing analysis software is cumbersome to use and often computationally inefficient. The ViPErLEED (Vienna package for Erlangen LEED) project lowers these barriers, introducing a combined solution for user-friendly data acquisition, extraction, and computational analysis. These parts are discussed in three separate publications. Here, the focus is on the computational part of ViPErLEED, which performs highly automated LEED-I(V) calculations and structural optimizations. Minimal user input is required, and the functionality is significantly enhanced compared to existing solutions. Computation is performed by embedding the existing Erlangen tensor-LEED package (TensErLEED). ViPErLEED manages additional parallelization, monitors convergence, and processes all input and output. This makes LEED I(V) more accessible to new users while minimizing the potential for errors and the manual labor. Added functionalities include intelligent structure-dependent defaults for most calculation parameters, automatic detection of bulk and surface symmetries and their relationship, automated search procedures that preserve the symmetry and speed up convergence, adjustments to the TensErLEED code to handle larger systems than before, as well as parallelization and optimization. Modern file formats are used as input and output, and there is a direct interface to the atomic simulation environment (ASE) package. The software is implemented primarily in Python (version ≥3.7) and provided as an open-source package (GNU GPLv3 or any later version). A structure determination of the α-Fe_{2}O_{3}(11[over ¯]02)-(1×1) surface is presented as an example for the application of the software.